Gestão logística em um evento cultural: estudo de caso da fantástica fábrica de Natal / Natal Luz de Gramado / RS - 27ª edição (2012 / 2013) - Strack, Adroaldo (2014)
Logistics has excelled in business as an essential element providing cost savings and competitive advantage. The logistics of events in turn acts in an area that requires bold and specific projects that move a significant number of professionals, tons of equipment, large financial investments, movement of people, demanding controls and developing strategies. In this scenario, the logistics of events is the subject of this study. Thus, this thesis aims to analyze logistics processes special event Fantastic Factory Christmas – Natal Luz de Gramado / RS in its 27th edition in the period 2012/2013. This study is qualitative in nature, exploratory studies, the following guiding the case study methodology. Data collection used as main sources to documentary research, individual interviews and observations. For data analysis we used the discursive textual analysis exploring the deductive, inductive and intuitive methods. The results of this study reveal deficiencies and needs for improvements in logistics processes in the areas of planning, efficiency used for modal shift, expansion of physical infrastructure, the use of available space and the use of reverse logistics post- event.